Capitalization of a Research Experience Masin: Instrument for Measuring Syntactic Maturity - Arce Cascante, Olga Patricia (2020)
This article is the result of an investigation, whose main objective was to determine the syntactic maturity in written productions of students from the ninth and tenth grades of Costa Rica secondary school, with a sample of 120 compositions from four schools: two public and two private centers. The research is based on the three basic measures of Kellogg W. Hunt’s ((1970a; 1970b; 1970c)) theoretical principles: T-unit average length (LP-UT), average clause length (LP-CL), and subordination index (IN-SUB). These three variables correlate with the following independent variables: the level of education (ninth and tenth year), the type of institution (public and private schools), sex, students with learning commitments (CCA), students without learning commitments (SCA), and type of curriculum adaptation (adaptation of accessibility, and significant and nonsignificant adaptations). The research integrates theoretical foundations of communicative competence, curriculum policy, and syntactic maturity. It also includes aspects related to the attention of diversity in classrooms and language acquisition based on Lev Vygotsky’s (1995) postulates. This study is about applied linguistics to education, and uses a descriptive research design of a correlational type. The research led to the creation of a program called syntactic maturity (MASIN) to be used by specialists of the language in a joint work with educators and educational psychologists, among others. It is also mentioned the convenience of didactic planning to enrich the different types of insertions, so that students use other options for the subordinating elements that the Spanish language has, especially in specific proposals of didactics of text for the introduction of subordinating adjectives and adverbs.